Thai Literature Instruction Using Readers Theater Strategy to Enhance Reading Comprehension Abilities of Secondary School Students - Saekee, Chutatip; Wongsuwan Kongpao, Wipawan (An Online Journal of Education, 2022)
The purposes of this research were to 1) compare the reading comprehension abilities of students before and after being instructed using the Readers Theater strategy, including both overall results and results from separated components, and 2) study the improvement in the reading comprehension abilities of the students who were instructed using the Readers Theater strategy. The sampling group was 43 seventh grade students in an extra-large secondary school in the Secondary Educational Service Area Office, Bangkok 2. The research instruments were an achievement test for evaluating the students’ reading comprehension abilities, a reading reflection form, and lesson plans for Thai literature instruction using the Readers Theater strategy. The research findings were as follows: 1) There were significant differences in the results between the pre-test and post-test scores of the students who were instructed using the Readers Theater strategy at the .01 level of significance, in which the mean of post-test scores was higher than the pre-test scores. Furthermore, it was found that there were seven components affected: translation, summarization, analysis, interpretation, valuation, connection, and transfer of the post-test scores were all higher than the pre-test scores at the .01 level of significance. 2) From the quality analysis to study the students’ progress in reading comprehension, it was found that the students who were instructed using the Readers Theater strategy showed improvement in all seven components of their reading comprehension abilities.